Analysis of Planning, Implementation, Management, Supervision, and Financial Accountability in Education at SD Negeri 155 Danau Saung Tantan - Margaretha, Dian; Jamil, Rahmat Pebrian; Elfina, Ira; Idrus, Ali (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to analyze the education funding cycle, which includes budget planning, budget implementation, financial management, budget oversight, and financial accountability at SD Negeri 155/IX Danau Saung Tantan. Research Methods: A qualitative case study approach was used. Data were collected through in-depth interviews, observations, and document analysis. Finding/Results: The results of the study indicate that the education financing cycle at the school has been carried out procedurally; however, it still faces a number of challenges, such as planning that is not yet fully based on actual needs, a financial management system that remains manual, delays in fund disbursement, suboptimal oversight, and a need to improve transparency and accountability toward all stakeholders. Conclusion: This study recommends optimizing needs-based planning, strengthening continuous oversight, utilizing information technology such as ARKAS, and increasing the disclosure of financial information to the public.